Teachers as Writers: A descriptive case study of my observations of English teachers in the middle school classroom - Honey, Haley (My University, 2020)
ABSTRACT For decades, numerous reports show a deficit in the American students’ ability to write well. Many sound recommendations, such as teachers acting as writers, have been made to improve the performance of students writing, yet sustained growth in student writing is infrequently reported. Data used comes from public middle school ELA teachers in the Southern United States. Data was collected during the 2019-2020 school year, before the COVID-19 pandemic. This study describes middle school English Language Art teachers as teacher-writers, specifically illustrating their experiences with writing and their approaches to teaching writing. I used a case study of four middle school ELA teachers at a singular site to describe teachers as writers. Data collected included interviews, focus group discussion, and observations. These were then analyzed using the constant comparative method to identify themes from individual teachers as well as draw comparisons across teachers. Results highlight significant differences in the four teachers experiences with writing and the significance their experiences play in their approach to teaching writing. Results indicate that, like students, teachers could be better served by specific learning opportunities that meet their needs as writers and as teachers of writing. Keywords: teachers as writers, middle school, writing
Keywords: writing; middle school; teachers as writers